Relict subduction initiation along a passive margin in the northwest Indian Ocean - Dhananjai K. Pandey (Nature Portfolio, 2019)
The tectonic evolution of the Laxmi basin, in the northwest Indian Ocean, remains controversial. Here, the authors present new geochemical and seismic data which indicate the Laxmi basin formed by a subduction initiation event during the break-up of Gondwana.